Quality of life as a measure of outcome in treatment of clients with PTSD following war related trauma - Ljubotina, Damir; Pantić, Zdenka; Frančišković, Tanja Kučukalić, Abdulah; Knežević, Goran Priebe, Stefan (2007)
517 clients with war trauma experience were included in a longitudinal study in several countries. All clients were interviewed at baseline and followed up after 3 and 12 months. The main goal of the study was to assess treatment outcomes in people included in formal psychotherapy and factors related with treatment outcomes. Measures of treatment outcome included level of PTSD symptoms (structured interview and scales), psychopathological dimensions and subjective quality of life. The study also assessed expectations of treatment, personality traits, coping strategies, treatment satisfaction and costs of health service. Quality of life is viewed as a multi-dimensional concept that incorporates dimensions referring to more than just an improvement or deterioration of clinical symptoms. Subjective quality of life is significantly correlated with other measures of posttraumatic symptoms, adaptive coping strategies, psychopathological dimensions, personality dimensions but low with level of traumatic experience. Results of the follow-up study show significant improvement in the first three months of therapy, but only for refugees, and no changes in the war veterans sample. Multivariate statistical analysis were used to identify most important predictors of quality of life, and levels of change during treatment.
Projekt MZOS
ENG